Design manufacturing integration and flight testing of a health monitoring system for a prototype unmanned airborne vehicle - Lawson, Craig P.; Al Monterzino, Guido (Sage, 2013)
This article describes the design, development, build and flight testing of a health monitoring system for the landing gear and the electrical power system on board the Demon prototype unmanned airborne vehicle. Demon is a flying technology demonstrator which successfully flew in September 2010. The Demon can achieve pitch and roll control without the use of hinged control surfaces, by instead using fluidic devices based on the Coanda effect, attaining low-maintenance, high-manoeuvrability operations. A vehicle health monitoring system was added on board between the first and the second flight test campaigns. The integration of the health monitoring system into the vehicle is discussed as a whole. The key health monitoring sub-systems include data logging and real-time measurement of several parameters. This includes systems to measure Voltage and current from the main batteries, landing gear stress, suspension travel, wheel hub acceleration and shock absorber pressure. Wherever possible, the use of commercially available components was maximised to minimise development time and cost. Some example results of system health monitoring during flight trials are presented
Keywords: Aerospace; unmanned airborne vehicle; health monitoring system